Friend or foe? Early life adversity to improve farmed animal welfare - Campbell, Dana L. M. (Frontiers in Animal Science, 2024)
Early life experiences can have lasting impacts on an animal’s development. Extensive research evidence aligns across both human and non-human rodent and primate laboratory animals showing negative impacts of early life adversity such as impairments in neurological and behavioural development. Farmed animals experience a range of adversities across their production lifetimes, often early in life, including species atypical social groupings, invasive husbandry procedures, and transport. Correspondingly, farmed animals also demonstrate a wide range of impairments such as stereotypic, injurious, and other abnormal behaviours. An individual, however, needs to experience adversity to be able to develop resilience and coping mechanisms that facilitate dealing with challenges later in life. Not all individuals will experience stress vulnerability following adversity, with some individuals instead developing stress resilience. This mini review collates evidence on the positive effects of early life adversity on improving adaptability in farmed species, both terrestrial and aquatic. While evidence across farmed animal species is currently much less than for humans, laboratory rodents or non-human primates, similar patterns emerge where mild adversity early in life, can improve the adaptability of the animal in the face of future stressors. Many views of optimised welfare posit that farmed animals should be housed in as natural environments as possible to limit many of the typical adversities they face. However, strategic mild exposure to early life adversity may facilitate improved animal welfare under intensive commercial farming conditions. Future research into this area could provide management tools to better predict and promote stress resilience over stress vulnerability.